Enhancing the Better Corporate Governance Practice From Accounting Scandals to Tax Risk Management - Přidal, Martin; Malý, Milan, 1936-; Jurka, Robert; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
Recent accounting scandals and current global financial crisis have brought new demands on the whole corporate world. The call for better corporate governance is strengthening in all business areas including tax. Tax non -- compliance brings substantial risks for both tax payers and tax revenue authorities. The way how companies manage their tax risks can significantly influence their overall financial performance and reputation. The paper deals with issues of tax non -- compliance as a lack of good corporate governance practice. The main goal of the paper is to put tax into the concept of corporate governance. Moreover, the paper deals with the concept of tax risk management as a way of how tax compliance in general could be enhanced and introduces the current international practice in this field.
Vedoucí práce: Milan Malý
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international Management [obor dipl. práce]; diplomové práce; master's theses